Improving Human Resources for Scout Trainers Through Basic Trainer Courses (KPD) - Anam, Khaerul (Jurnal Pengabdian Masyarakat Formosa, 2024)
This service focuses on improving the quality of Scout trainers through the implementation of the Basic Scout Trainer Course (KPD). The methodology used includes pre-tests and the provision of materials for 8 days, followed by a post-test to assess the final results. The service results show an initial average understanding of 70% regarding the tasks and roles as trainers. After the training, there is a significant increase of 95% in the quality and effectiveness of training following the implementation of the Basic Scout Trainer Course (KPD). This has a positive impact on trainer competence and the overall quality of Scout programs. This service advocates for the adoption of the Basic Scout Trainer Course (KPD) as the minimum standard for Scout trainer training.